2019
DOI: 10.1002/er.5082
|View full text |Cite
|
Sign up to set email alerts
|

Predictive energy management for a wind turbine with hybrid energy storage system

Abstract: Summary Hybrid energy storage systems (HESSs) help mitigating the fluctuations and variable availability of certain renewable sources, such as wind power, as they can provide support in different time scales. Therefore, regulating their state‐of‐charge (SOC) becomes crucial to ensure that the hybrid system complies with generation commitments agreed in time‐ahead markets despite subsequent unexpected wind speed variations. So far, research has been mainly targeted at avoiding extreme SOC situations in the stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The essential role of the supervisory controller is to satisfy the loads demand without interruption under variable weather conditions, by managing the power flow of the IHPS [19][20][21][22][23]. The proposed energy management algorithm uses primarily the power provided by the PVS and WECS to supply the load, and minimizes the use of the batteries and DG for optimizing of fuel consumption and saving the environment.…”
Section: -Energy Management System For Ihpsmentioning
confidence: 99%
“…The essential role of the supervisory controller is to satisfy the loads demand without interruption under variable weather conditions, by managing the power flow of the IHPS [19][20][21][22][23]. The proposed energy management algorithm uses primarily the power provided by the PVS and WECS to supply the load, and minimizes the use of the batteries and DG for optimizing of fuel consumption and saving the environment.…”
Section: -Energy Management System For Ihpsmentioning
confidence: 99%
“…The cost function is defined by (9). This function must comply with (10) and the restrictions in (11). (11) where the power limits of the BES are denoted as −P max BES (maximum discharging power) and P max BES (maximum charging power), and the power limits of the hydrogen system are denoted as −P max ELZ (maximum power absorbed by the EZ) and P max FC (maximum power generated by the FC).…”
Section: A Cost Calculation Systemmentioning
confidence: 99%
“…Model predictive control (MPC) as an EMS in hybrid power systems combining renewable resources and ESS has been applied in several studies. In [11], a MPC-based EMS was used to regulate the SOC of an ultracapacitor. In this study, the costs of the system were not considered, and short-term operation was considered.…”
Section: Introductionmentioning
confidence: 99%
“…While wind power accessing the grid, the generator will put a very strong pulse current, which will easily lead to the shutdown or failure of the electrical equipment of the access circuit 74 . Studies have shown that hybrid energy storage systems can mitigate fluctuations and variable availability of certain renewable resources such as wind energy, because they can provide support in different time frames 75 . It is necessary to establish a energy storage system to smooth power fluctuations and further increase costs.…”
Section: Advantages and Constraints Of Owecmentioning
confidence: 99%